A survey study of educators’ and teachers’ opinions about gifted students and their education - Olivieri, Diana (Formazione & insegnamento, 2018)
Why is there resistance to identify first, and then support gifted children in our regular classes? Why feeding “suspicion” of those who show high levels of intelligence, especially if very precocious? Labeling theory and the stereotype threat can help in trying to answer these questions. If labels are the names we attribute to people, stereotypes are the social expectations associated with those labels. If a school label is strengthened enough for students to derive their identity from it, it will also influence their social interactions in and outside school. Thus, it’s pivotal to understand educators’ and teachers’ attitudes toward giftedness and gifted education. Adequate educational services for gifted students require simultaneous provision of gifted instruction and special education, ie strategies, adaptations and teaching practices necessary for students who, in their own way, have special needs.